Multi-criteria evaluation of innovative projects by means of ELECTRE application - Vysochan, Oleh; Vysochan, Olha; Hyk, Vasyl; Boychuk, Andriy (Business: Theory and Practice, 2022)
The purpose of this article is to study the possibilities of using multi-criteria decision-making tools (MCDM), a separate method of multi-criteria analysis (MCA), to evaluate and rank a set of innovative projects that come to innovation development programs, microorganisms. To assess the relative effectiveness of the implementation of innovative projects of the enterprise using the method of the ELECTRE family, namely – ELECTRE-I. The study demonstrated the effectiveness of using ELECTRE-analysis to evaluate innovative projects within the program of innovative development of the enterprise,taking into account performance (benefit factor), time (cost factor) and resources (cost factor). The study concerned a specific machine-building enterprise to prove the possibility of implementing the ELECTRE method and obtain clear results while expanding the input analytical information in the model by including data from other enterprises of the machine-building industry of Ukraine, which will be the subject of our further research. To build a weighted normalized matrix in the framework of ELECTRE-analysis used weights obtained by interviewing managers of innovative projects of the enterprise, which suggests the presence of a certain level of subjectivity in the assessment. The article is designed to close the gaps in the lack of practical experience in using the tools of multi-criteria analysis to establish the relative effectiveness of the implementation of a set of projects in the program of innovative development of Ukrainian enterprises.